DESIGNING A PROMOTION MEDIA OF SMP SANTA MARIA II SIDOARJO - Worabai, Dave Edwards Maurgi; Arumsari, Rizki Yantami; Nurbani, Sri (Telkom University, 2024)
The advancement of science and technology mandates adaptive change to stay current. Knowledge's pivotal role in enhancing societal competitiveness is recognized. Education is a strategic tool, fostering intelligence, skills, and positive attitudes for effective societal integration. Schools, through education, cultivate human potential and form positive identities. Law 20/2003 defines education as a means todevelop human potential. Education's root in